2013
DOI: 10.1097/iae.0b013e318285cc52
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Functional Evaluations During Development, Resolution, and Relapse of Uveitis-Associated Cystoid Macular Edema

Abstract: Different morphologic patterns in uvCME may represent different stages in uvCME progression, and initial morphologic appearance can be linked to the clinical prognosis after the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
2
29
0
3
Order By: Relevance
“…Furthermore, Sigler et al 22 supposed that the earliest retinal damage involved the INL with cystic changes and then the OPL and subretinal space. This pattern was very similar to that of active uveitic CMO,23 supporting again the inflammatory pathogenesis of PCMO. Nevertheless, FA has the limitation that cannot well visualise the DCP,10 which is the main retinal vascular layer altered in PCMO.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, Sigler et al 22 supposed that the earliest retinal damage involved the INL with cystic changes and then the OPL and subretinal space. This pattern was very similar to that of active uveitic CMO,23 supporting again the inflammatory pathogenesis of PCMO. Nevertheless, FA has the limitation that cannot well visualise the DCP,10 which is the main retinal vascular layer altered in PCMO.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies of epiretinal membranes and uveitic macular edema also have found that epiretinal membranes limit the response to therapy, as eyes with epiretinal membranes had significantly worse acuity at 3 months after intravitreal triamcinolone acetonide injection 9 and were significantly more likely to fail medical therapy for uveitic macular edema. 10 Our data, though limited by sample size, support this concept.…”
Section: Discussionmentioning
confidence: 84%
“…7,8 Detrimental clinical effects of epiretinal membrane formation on uveitic macular edema have been described. Epiretinal membranes have been associated with worse visual acuity in uveitic macular edema patients 3 months after treatment with intravitreal triamcinolone acetonide, 9 as well as a higher risk of failing medical therapy for uveitic macular edema. 10 In one study, foveal involvement of the epiretinal membrane and focal attachment of the epiretinal membrane to the inner retinal surface were predictors of poor vision.…”
mentioning
confidence: 99%
“…Besides detection of various macular pathologies, measurement of general anatomical indices such as central retinal thickness (CRT) and macular volume (MV) has been correlated in previous studies with visual acuity and response to therapy. 2,3 While previous studies using SD-OCT focused on uveitis patients with manifest secondary changes of the retina, primarily CME, [2][3][4][5][6][7][8][9][10][11][12][13][14] we were interested to analyze the macular morphology in a large series of consecutive patients with different types of uveitis, using SD-OCT. We assessed the CRT, MV, and presence of cystoid macular edema (CME), diffuse macular edema (DME), serous retinal detachment (SRD), ERM with (ERM+) and ERM without (ERM − ) retinal surface wrinkling.…”
Section: Introductionmentioning
confidence: 99%